Designing a Blockchain-based SME transaction model using the Federated Byzantine Agreement to shorten transaction validation times - Bernardinus Harnadi; Erdhi Widyarto (SISFORMA, 2023)
Since the world experienced the Covid-19 pandemic, the role of MSMEs in the e-commerce sector has grown rapidly and contributed 50% of Indonesia's GDP. However, investors and some consumers still underestimate MSMEs. They have a low level of trust in MSMEs. This is due to the lack of a transparent system so that cases of fraud against MSME products often occur. This issue of trust and transparency needs to be resolved with technological solutions. One technology that can solve this problem is Blockchain. However, currently there are still validation problems if it is to be implemented in MSMEs. This research aims to resolve validation time constraints in the implementation of MSMEs. This research builds a Blockchain-based MSME transaction model using Federated Byzantine Agreement (FBA) algorithm to solve validation time problems. The result shows that FBA is able to complete transactions with the fastest validation time compared to Proof of Work (POW), Proof of State (POS), and Proof of Authority (POA).